THE MANIFESTATION OF METAPHYSICAL FEATURES IN TED HUGHES' POETRY - Qurbonova Nodira Roziqovna; Ikromova Nozima Ilhomovna (Web of Journals Publishing, 2025)
This study explores the metaphysical elements in Ted Hughes' poetry, highlighting how his works reflect deep existential themes. Hughes, known for his powerful imagery and nature-centric poetry, frequently bridges the physical and spiritual worlds. His poems, such as The Thought-Fox, Thrushes, and Pike, incorporate themes of inspiration, survival, violence, and death, resonating with the traditions of metaphysical poetry. While Hughes is not classified as a metaphysical poet in the traditional sense, his works exhibit intellectual depth, symbolic richness, and philosophical exploration, aligning him with the metaphysical tradition.
Keywords: Metaphysical poetry, existential themes, inspiration, survival, violence, death, symbols, nature, philosophical exploration, imagery power.